Beyond all expectations : the story of Paige Barton - Putnam, JoAnne W. (JoAnne Wachholz) (Orono, Me. : University of Maine Center for Community Inclusion, 2003)
The Story of Paige Barton is the remarkable story of how Paige overcame tremendous societal barriers to gain independence from institutions, obtain her Bachelor's degree, and earn a professional position in state government advocating for people with disabilities.
Paige Barton lived in Skowhegan, Augusta, and Biddeford, and graduated from the University of Maine, Farmington. JoAnne Putnam is a Professor of Teacher Education at the University of Maine at Presque Isle.
Keywords: Barton, Paige -- Mental health; People with mental disabilities -- Biography; People with disabilities -- Biography